Volatility, Information and Stock Market Crashes - Nikolaos Antonakakis; Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2009)
In this paper, we examine the evolution of the S&P500 returns volatility around market crashes using a Markov-Switching model. We find that volatility typically switches into the high volatility state well before a crash and remains in the high state for a considerable period of time after the crash. These results do not support the view that crashes are due to the resolution of uncertainty (e.g. Romer, 1993), but are consistent with the model in Frankel (2008) where the adaptive forecasts of volatility by uniformed traders result in a crash.
Keywords: C11; D8; G0; 330; Stock Market Crash; Volatility; Markov Switching; Börsenkrise; Kapitalertrag; Börsenkurs; Volatilität; Markovscher Prozess; USA